Pemberdayaan Masyarakat Melalui Pengolahan Batang Pisang Menjadi Benang Sebagai Bahan Baku Kain dan Industri Kreatif - Siti Nikmatin; Abd Djamil Husin; Rima Fitria Adiati (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to improve the economy of the village community and bring biomaterial research innovation results through the processing of banana stems into yarn as a raw material for cloth and the creative industry. The method of implementing this service used training which consisted of the stages of program introduction, processing of banana stem waste, and commercialization. The partners for this activity were the people in Sidorejo Village, Sukosewu District, Bojonegoro Regency, which are members of youth organizations. The results of this community service activity were analyzed descriptively, and simple banana stem processing positively impacted new knowledge and sources of income. The people of Siderejo village got additional daily income, activities for local economic development, and added value in knowledge, affective, and motor skills.